Quality of human phenotypes in patients with intellectual disabilities undergoing exome sequencing tests at a Peruvian pediatric hospital - Custodio-Sánchez, Pedro (2024)
Introduction. Massive sequencing and the Human Phenotype Ontology have revolutionized genetic diagnosis, allowing for a clearer understanding of diseases. The phenotypes described in medical records can be specific or general, the more detailed and specific the description, the higher the quality of the information. Objectives. To determine the relationship between the quality of human phenotypes in patients with intellectual disability and the findings from massive sequencing test at the Instituto Nacional de Salud del Niño. Methods. We analyzed 124 patients with intellectual disabilities with exome sequencing. The quality of human phenotypes was evaluated using different quality index. Results. A total of 278 human phenotype terms were identified. Phenotypic precision improved after filtering, highlighting the importance of specific phenotypic descriptions (from 103 to 86 unique terms). The specificity index of the dataset was lower in the group with variants of uncertain significance compared to the group with pathogenic variants (0 vs. 0.05). The most frequent phenotypes were psychomotor delay (12.9% - 15.9%) and microcephaly (4.5% - 5.2%). Conclusions. The importance of evaluating the quality of human phenotypes is highlighted. The presence of uncertain variants suggests a genotype-phenotype complexity, emphasizing the need for greater clarity in genetic interpretation. Consistency in confidence intervals and the specificity index of the dataset underscores the competence of local medical-genetic personnel.